Impact of the COVID-19 pandemic on children's mental health: A systematic review - Ng, Catalina Sau Man; Ng, Sally Sui Ling (Frontiers in Psychiatry, 2022)
Background: The outbreak of COVID-19 in December 2019 has caused unprecedented disruption to the structure of children’s daily lives due to school closures, online learning, strict social distancing measures, limited access to outdoor activities and many other restrictions. Since children are more susceptible to stress than adults and there is a growing concern about the potential debilitating consequences of COVID-19 for children’s mental health, the present review aims to provide empirical evidence on the groups who are most at risk of mental health problems and uncover the risk and protective factors of children’s mental health. Methods: A systematic search was performed, in accordance with PRISMA guidelines, in the electronic databases Web of Science (including SSCI and A&HI) and EBSCOhost (including ERIC, MEDLINE and APA PsycArticles and APA PsycINFO), for any empirical studies published between January 2020 and February 2022 that focused on children ≤ 12 years old. Results: An initial search identified 2,133 studies. A total of 30 studies fulfilled the inclusion criteria and were analyzed. The evidence showed that many children were affected by the COVID-19 pandemic and experienced internalizing and externalizing behaviors. Worsened child mental health outcomes reflected socioeconomic inequalities as most at-risk children had parents with low educational attainment, were from families of low socioeconomic status and lived in small homes. Key risk factors were identified, including unhealthy lifestyle behaviors (extended screen time, sleep disturbances and less physical activity), increased pandemic-related stressors among parents and deteriorated mental health of parents, which were directly or indirectly associated with the pandemic safety measures, such as home confinement or social distancing. Protective factors including parents’ resilience, positive parent-child relationship and school connectedness in relation to children’s mental health were reported. Conclusion: The overall results highlight the urgent need for the implementation of tailor-made interventions for children with signs of internalizing and externalizing behaviors. Health promotion and prevention strategies by the government to maintain the mental health of children, particularly those from lower SES families who are at higher risk of worsened mental health are essential for post-pandemic policies.